A Maqasid Sharia Analysis of Item Purchase Practices in the Roblox Game - Muhamad Nuruzzaman; Dede Wildan; Sulthan Arfa Almalik; Jaenudin J; Dian Herdiana (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the practice of purchasing digital items in the Roblox game from the perspective of maqasid al-syari‘ah, with a specific focus on the principle of protection of wealth. Using a qualitative descriptive method and a maqasid-based analytical approach, this research explores players’ consumption behavior, motivations, and the ethical dimensions of digital spending. Data were obtained through interviews with two Roblox players and an academic expert, supported by relevant literature. The findings show that the purchase of Robux and in-game items is generally conducted for recreational purposes and remains within acceptable financial limits when basic needs are fulfilled and spending is controlled. While such transactions are categorized as permissible according to Islamic economic principles, they carry potential risks such as impulsive spending, digital addiction, and exposure to inappropriate content. The study concludes that purchasing digital items in Roblox is allowed as long as it does not lead to wastefulness, harm, or neglect of obligations. Implementing moderation and financial awareness is essential to ensure alignment with maqasid al-syari‘ah, particularly in protecting wealth and preserving moral values within digital consumption practices.